A critical review of the 15N2 tracer method to measure diazotrophic production in pelagic ecosystems. (12th March 2020) - White, Angelicque E.; Granger, Julie; Selden, Corday; Gradoville, Mary R.; Potts, Lindsey; Bourbonnais, Annie; Fulweiler, Robinson W.; Knapp, Angela N.; Mohr, Wiebke; Moisander, Pia H.; Tobias, Craig R.; Caffin, Mathieu; et al.
Abstract: Dinitrogen (N2 ) fixation is an important source of biologically reactive nitrogen (N) to the global ocean. The magnitude of this flux, however, remains uncertain, in part because N2 fixation rates have been estimated following divergent protocols and because associated levels of uncertainty are seldom reported—confounding comparison and extrapolation of rate measurements. A growing number of reports of relatively low but potentially significant rates of N2 fixation in regions such as oxygen minimum zones, the mesopelagic water column of the tropical and subtropical oceans, and polar waters further highlights the need for standardized methodological protocols for measurements of N2 fixation rates and for calculations of detection limits and propagated error terms. To this end, we examine current protocols of the 15 N2 tracer method used for estimating diazotrophic rates, present results of experiments testing the validity of specific practices, and describe established metrics for reporting detection limits. We put forth a set of recommendations for best practices to estimate N2 fixation rates using 15 N2 tracer, with the goal of fostering transparency in reporting sources of uncertainty in estimates, and to render N2 fixation rate estimates intercomparable among studies.